Empirical superior vena cava isolation in patients undergoing repeat catheter ablation procedure after recurrence of atrial fibrillation - Simu, Gelu; Deneke, Thomas; Ene, Elena; Nentwich, Karin; Berkovitz, Artur; Sonne, Kai; Halbfaß, Philipp; Arvaniti, Eleni; Waechter, Christian; Müller, Julian (Journal of interventional cardiac electrophysiology, 2022)
Background: Although the ectopic foci responsible for initiating atrial fibrillation (AF) are usually located in the pulmonary veins (PVs), non-PV sources may initiate AF in approximately 11% of unselected patients with paroxysmal or persistent AF. The superior vena cava (SVC) is one of the most frequent non-PV origins for initiating AF. This study aims to investigate the effect of empirical SVC isolation in redo AF ablation procedures. Methods: Consecutive patients undergoing redo AF ablation procedures using a high-power short-duration protocol (HPSD) (50 W; ablation index guided; target AI 350 for posterior wall ablation, AI 450 for anterior wall ablation; CARTO 3 mapping system) were included. Patients with SVC isolation were compared to patients without SVC isolation. Periprocedural parameters and complications were recorded and analyzed. Short-term endpoints included intrahospital AF recurrence, midterm endpoint AF freedom after 3 months, and long-term endpoint AF freedom after 12 months. Results: A total of 276 patients underwent repeat ablation for recurrent AF (67 ± 10 years; 57% male; 31.5% paroxysmal AF). The patients were divided into two groups: redo procedures with SVC isolation vs redo procedure without SVC isolation. Additional LA substrate modification was done based on intraprocedural voltage maps. Baseline characteristics did not differ significantly between the two groups. Median procedure time was 85.4 ± 27.1 min with ablation times of 14.0 ± 8.5 min. Intrahospital AF recurrence occurred in 32 patients (12%) with no difference among both groups: 17 patients (13%) SVC vs 15 patients (10%) No-SVC; p = 0.416. At 3-month follow-up, 47 (17%) presented an AF recurrence during the blanking period: 25 patients (19%) SVC vs 22 patients (15%) No-SVC; p = 0.304). After 12 months, 202 (73%) of all patients were in stable sinus rhythm with no significant difference between the two groups: 93 patients (73%) SVC vs 109 patients (74%) No-SVC; p = 0.853). No significant differences were noted when dividing the patients in paroxysmal or persistent AF with and without SVC isolation. Conclusions: In our series of repeat AF ablation procedures, the addition of empirical SVC isolation to Re-PVI and LA substrate modification did not influence AF recurrence rates. This strategy can however be safe and useful in patients in whom SVC is identified as a trigger of AF.
Gesehen am 25.07.2023